Population-Level Herd Protection of Males From a Female Human Papillomavirus Vaccination Program: Evidence from Australian Serosurveillance. (3rd July 2017) - Pillsbury, Alexis J; Quinn, Helen E; Evans, TaNisha D; McIntyre, Peter B; Brotherton, Julia M L
Summary: Existing evidence of a male herd protection impact from female human papillomavirus (HPV) vaccination comes from genital-wart and HPV infection studies. This is the first evidence from population-level immunity changes supporting an indirect effect in males temporally associated with female vaccination. Abstract: Background: Australia instituted funded female human papillomavirus (HPV) immunization in 2007, followed by a targeted male vaccination program in 2013. To date, Australia is one of only several countries with a funded male HPV immunization program. In 2012–2013, we conducted a survey of HPV seroprevalence in males to assess whether or not a herd impact of female vaccination could be observed. Methods: We conducted a cross-sectional study of de-identified residual diagnostic test serum samples from males aged 15–39 years from laboratories in 3 Australian states and calculated the proportion seropositive to HPV types 6, 11, 16, and 18. We compared type-specific results by age group against those from a baseline 2005 Australian HPV serosurvey. Results: There were decreases in proportion seropositive for every HPV type across all age groups, many statistically significant. The largest decrease was observed for HPV-11, with decreases of 8- and 9-fold for ages 20–29 and 30–39 years, respectively. Despite substantial reductions in seroprevalence, at least 9% of males were seropositive for at least 1 of the 4 HPV types. Conclusions: This is the first serosurvey confirming broad population-level impact in males from female HPV vaccination. Our research may assist policy makers considering implementing HPV vaccination programs.